Economic Growth Dynamics in Central Sulawesi: The Role of Public Spending, Inequality, and Socio-Economic Factors - Farida Millias Tuty; Chairil Anwar; Moh. Ahlis Djirimu (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This research examines the patterns of economic development in Central Sulawesi, emphasizing the impact of capital spending, wealth disparity, poverty levels, historical Gross Regional Domestic Product, joblessness, and the Human Development Index. The investigation employs panel data from districts and cities spanning 2016-2021, utilizing a dynamic panel regression approach to assess how lagged independent variables affect contemporary economic expansion. Analysis findings demonstrate that municipal capital investments significantly and positively influence economic development, suggesting that government expenditure on infrastructure and human capital serves as a primary catalyst for enhanced regional economic performance. On the other hand, income inequality and unemployment have a significant negative influence, indicating that social inequality and low labor utilization are obstacles to growth. The poverty and Human Development Index variables showed a not significant influence, indicating the need for further studies related to the mediation variables and a longer observation period. Past Gross Regional Domestic Product has also been shown to have a significant positive effect, confirming the effect of temporal dependence in the regional economic development process. These findings strengthen the understanding of the importance of effective fiscal policies and efforts to reduce inequality and unemployment to promote inclusive and sustainable economic growth in Central Sulawesi.